The Role of The Ministry of Defense in Ensuring Food Security for State Defense - Aris Sarjito (Universitas Sultan Ageng Tirtayasa, 2022)
The development of global dynamics has led to a shift in the security paradigm, one of which is in the food sector. Based on FAO's qualification for food security, Indonesia is at a relatively stable point in its food security index. But this is also a concern for the government considering that Indonesia is also experiencing a period of Covid 19 which forces food consumption to increase. The appointment of the Ministry of Defense as the leading sector in the food sector is a strategic policy of the government with regard to the country's defense in non-military threats. This paper uses role theory, defense concepts and food security concepts in discussing the topic. The results of this study saw that Indonesia's food security index from the availability aspect reached a score of 67.36, aspects of food access (79.56), utilization aspects (67.97) and food stability (72.11). The appointment of the Ministry of Defense as the leading sector places Central Kalimantan as a food estate considering that the province has a relatively sufficient food availability score. Central Kalimantan is projected to be a source of food reserves for areas that lack food index so that food stability in Indonesia can increase.